International Interventions to Build Social Capital : Evidence from a Field Experiment in Sudan - Avdeenko, Alexandra; Gilligan, Michael J. (World Bank, Washington, DC, 2014)
Over the past decade the international community, especially the World Bank, has conducted programs to increase local public service delivery in developing countries by improving local governing institutions and creating social capital. This paper evaluates one such program in Sudan to answer the question: Can the international community change the grassroots civic culture of developing countries to increase social capital? The paper offers three contributions. First, it uses lab-in-the-field measures to focus on the effects of the program on pro-social preferences without the confounding influence of any program- induced changes on local governing institutions. Second, it tests whether the program led to denser social networks in recipient communities. Based on these two measures, the effect of the program was a precisely estimated zero. However, in a retrospective survey, respondents from program communities characterized their behavior as being more pro-social and their communities more socially cohesive. This leads to a third contribution of the paper: it provides evidence for the hypothesis, stated by several scholars in the literature, that retrospective survey measures of social capital over biased evidence of a positive effect of these programs. Regardless of one's faith in retrospective self-reported survey measures, the results clearly point to zero impact of the program on pro-social preferences and social network density. Therefore, if the increase in self-reported behaviors is accurate, it must be because of social sanctions that enforce compliance with pro-social norms through mechanisms other than the social networks that were measured.